Diffusion MRI fibre orientation dispersion estimates evaluated with polarized light imaging and histological analysis - Mollink, J; Kleinnijenhuis, M; Pallebage-Gamarallage, M (FMRIB Centre, University of Oxford, 2017)
This data was collected for a study that evaluated fibre orientation dispersion estimates from diffusion MRI in white matter of the brain against two microscopy techniques, i.e. polarized light imaging and histological stainings for myelin and astrocytes. Raw and processed data is available including the processing pipelines. More information about the data can be found in the README.txt file.